Perlindungan Hukum Terhadap Lead Bank Dalam Terjadinya Wanprestasi Kredit Sindikasi di Kota Batam - Jessca Jessca; Rufinus Hotmaulana Hutauruk; Hari Sutra Disemadi (JURNAL HUKUM PELITA, 2025)
Syndicated credit refers to the provision of credit extended by more than one rural bank (BPR) for a single debtor loan. In Batam City, this type of credit is commonly practiced by BPRs to meet the needs of debtors requiring large loans. In this mechanism, one bank acts as the lead bank, serving as the principal institution leading the syndicated credit provision. This study provides an overview of the implementation of dispute resolution in syndicated credit in the event of default by the debtor, as well as the legal protection afforded to the lead bank during the dispute resolution process. The findings indicate that the resolution of syndicated credit disputes resulting from debtor defaults is effectively conducted through negotiation. The lead bank plays an active role in openly assisting the debtor to find the best solution to fulfill their obligations. Moreover, the lead bank is granted legal protection in resolving syndicated credit disputes, as stipulated in the syndicated credit agreement signed before the credit is extended to the debtor. This legal protection is highly effective in addressing default disputes, thereby safeguarding the lead bank from potential losses